Critical criminological research on environmental and social harm: some lessons learnt and suggestions for future research - Ronco, Anna Di (Criminological encounters, 2021)
In this short article, I highlight the main methodological contributions of our recent research on the uses of Twitter by the criminalised environmental movement NOTAP in Italy and the intersections between online and offline representations of their protesting. As I illustrate in this piece, when studying activist technosocial practice, innovative computational tools - such as the ones we used in our studies - can facilitate the collection and sorting of important social media material related to activist practice online, which can go a long way into uncovering unrecognized sources of harm and suffering, often obscured by mainstream media. As our research demonstrates, however, to be able to comprehensively capture activist practice and, specifically, activists’ lived experiences of social control, social media research should always be combined with on-the-ground qualitative ethnographic research. To assist to the latter end, critical criminologists can also rely on a recent and quite innovative repertoire of sensory and participative (itinerant) methodologies, which I address in the final part of the article.